Pengaruh Manajemen Pengetahuan Terhadap Kinerja Inovasi - Simbolon, Oslan Juliana; Sitanggang, Lestari Pratiwi; Trisanti, Ayu; Sinurat, Indriyani; Br Tarigan , Miska Irani (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
The increasingly dynamic and competitive global economy has shifted the organizational paradigm from resource-based management to knowledge- based management. Knowledge has become a strategic asset that determines an organization’s innovation capacity and competitive advantage. In the regional context, particularly in Southeast Asia, digital transformation has intensified the need for effective knowledge management (KM) practices to strengthen organizational innovation performance. This study aims to examine the influence of knowledge management on innovation performance. A systematic review approach was applied to analyze empirical and theoretical studies published between 2018 and 2025 from Scopus-indexed journals, nationally accredited journals (SINTA 1–2), and recent academic books. The study employed content analysis based on the PRISMA protocol (Preferred Reporting Items for Systematic Reviews and Meta-Analyses), focusing on the processes of knowledge creation, sharing, storage, and application, and their impacts on innovation outcomes. The results show that effective knowledge sharing and application practices have a significant positive impact on both product and process innovation performance. Additionally, organizational culture and transformational leadership serve as mediating factors that strengthen the relationship between knowledge management and innovation. The key findings highlight that the integration of digital knowledge systems and organizational learning behavior supports sustainable innovation development. This study concludes that organizations should develop adaptive knowledge management strategies supported by robust technological infrastructure and human resource capabilities focused on continuous learning. Recommendations are provided for managers and policymakers to position knowledge management as a strategic foundation for achieving sustainable innovation excellence.